ORF6 of Tobacco mosaic virus is a determinant of viral pathogenicity in Nicotiana benthamiana - Canto, Tomas; MacFarlane, Stuart A.; Palukaitis, Peter (Journal of General Virology, 2004)
Tobacco mosaic virus (TMV) contains a sixth open reading frame (ORF6) that potentially encodes a 4·8 kDa protein. Elimination of ORF6 from TMV attenuated host responses in Nicotiana benthamiana without alteration in virus accumulation. Furthermore, heterologous expression of TMV ORF6 from either potato virus X (PVX) or tobacco rattle virus (TRV) vectors enhanced the virulence of both viruses in N. benthamiana, also without effects on their accumulation. By contrast, the presence or absence of TMV ORF6 had no effect on host response or virus accumulation in N. tabacum plants infected with TMV or PVX. TMV ORF6 also had no effect on the synergism between TMV and PVX in N. tabacum. However, the presence of the TMV ORF6 did have an effect on the pathogenicity of a TRV vector in N. tabacum. In three different types of assay carried out in N. benthamiana plants, expression of TMV ORF6 failed to suppress gene silencing. Expression in N. benthamiana epidermal cells of the encoded 4·8 kDa protein fused to the green fluorescent protein at either end showed, in addition to widespread cytosolic fluorescence, plasmodesmatal targeting specific to both fusion constructs. The role of the ORF6 in host responses is discussed.